Diagnosing skull fracture in children with closed head injury using point-of-care ultrasound vs. computed tomography scan - Dehbozorgi, Afsaneh (Eur J Pediatr, 2020)
Diagnostic and therapeutic interventions in children for traumatic brain injury, which is known as the most important complication in trauma, require special attention. This study aimed to evaluate the accuracy of point-of-care ultrasound (POCUS) in diagnosing skull fracture in children with closed head injury in comparison with computed tomography (CT) scan. The current prospective cross-sectional study was conducted on children (0–14 years old), who were referred to the emergency department of a general teaching hospital in Shiraz, southern Iran (January–March 2018), with close head injury and were suspected of bone fracture. The participants were selected using a convenience sampling. The results of POCUS performed by emergency medicine (EM) residents were compared with the results of CT scan, which was reported by radiologists and considered a gold standard. Then, diagnostic tests were calculated. A total of 168 children were enrolled, with the mean ± standard deviation age of 6.21 ± 3.99. The most affected areas in the skull were the frontal (34.5%) and occipital areas (33.3%). POCUS had a sensitivity and specificity of 81.8% (95%CI, 48.2–97.7%) and 100% (95%CI, 97.7–100%), respectively. Positive and negative predictive values were 100% and 98.7%, with an accuracy of 98.8% in comparison with CT scan in the diagnosis of skull fracture. Conclusion: The results showed that POCUS with a portable ultrasonography machine, performed by the EM’s physicians, have high diagnostic precision and can be considered a tool in the management of patients with closed head injury.